Marine Drugs: A Review - Gupta, Muskan; Kumari, Annu; Rankawat, Abhishek; Rankawat, Gaurav (Asian Journal of Pharmaceutical Research and Development, 2023)
As all of usrecognizebecause ofbigimprovement of the sectorpopulacenumerouspresentreassets of the drug are diminishing and drug builders and producers are looking at for the brand newsources to increase new capsuleswhich aresecure and valuepowerful and effectively meet the growingcall for of world.Marine pharmacognosy gives the scope for studies on thosecapsules on marine origin. As we know marine monographs are very less compared to herbal monographs. Therefore an attempt has been made to explore knowledge on marine pharmacognosy. This assessmentspecializes in marine sources, type of drug molecule of marine organism, numerous marine tabletswith inside themarketplace and strategies to extract numerous biomolecules from seafood waste.